Creativity in translating cartoons for children from English into Mandarin Chinese - Song Cui (JoSTrans: The Journal of Specialised Translation)
Cartoon translation appears to be a special field in screen translation. It can be argued that when translating cartoons, especially those for children, creativity in use of the target language could be explored, and a certain degree of re-writing of the language in the dialogue could be acceptable, so that strategies should be applied to achieve the effect that the translated version sounds natural, educational and entertaining to the target language audience. This paper examines some aspects of this special field of translation, including ideology issues, domestic culture awareness and the translator's active choice of creative language in their translation, to suggest that approaches such as domestication, or "excessive domestication" as the author of this paper defines, and cultural adaptation provide ways in which translators implement their creativity when translating cartoons. The discussion is exemplified by excerpts from cartoon translation from English into Mandarin Chinese.